Internationalizing Media Studies - Thussu, Daya Kishan (Internationalizing Media Studies, 2009)
The explosion of transnational information flows, made possible by new technologies and institutional changes (economic, political and legal) has profoundly affected the study of global media. At the same time, the globalization of media combined with the globalization of higher education means that the research and teaching of the subject faces immediate and profound challenges, not only as the subject of enquiry but also as the means by which researchers and students undertake their studies. Edited by a leading scholar of global communication, this collection of essays by internationally-acclaimed scholars from around the world aims to stimulate a debate about the imperatives for internationalizing media studies by broadening its remit, including innovative research methodologies, taking account of regional and national specificities and pedagogic necessities warranted by the changing profile of students and researchers and the unprecedented growth of media in the non-Western world. Transnational in its perspectives, Internationalizing Media Studies is a much-needed guide to the internationalization of media and its study in a global context. "For far too long, media studies has been dominated by people who could only research and write in English. The result has been effortless extrapolations from very specific realities (the US and the UK) to explain the entire, rich (and poor) world of the media. That is no longer sustainable, as Daya Thussu and his contributors show us in this dynamic and profound book. A way forward for all." Toby Miller, Professor of Media and Cultural Studies, University of California, Riverside, USA "Globalization poses dramatic new challenges for media studies, challenges that most scholars have failed to take up. This impressive collection of essays ranges across disciplines, methodologies, and geographical contexts to suggest important new directions for research and pedagogy in the field of media studies." Michael Curtin, Mellichamp Professor of Global Media Studies, University of Wisconsin-Madison, USA "This is a timely and pertinent reflection on media going global by leading scholars in the field, probing and critical." Jan Nederveen Pieterse, Mellichamp Professor of Global Studies and Sociology, University of Illinois at Urbana-Champaign, USA Daya Kishan Thussu is Professor of International Communication at the University of Westminster in London . The founder and Managing Editor of the journal Global Media and Communication, his key publications include News as Entertainment; Media on the Move; International Communication, and Electronic Empires. Introduction. Daya Kishan Thussu. Part I. Internationalizing Media Research 1. Why Internationalize Media Studies and How? 2. What Should Comparative Media Research Be Comparing? Towards a Transcultural Approach to ‘Media Cultures’ 3. Globalization Theories and Media Internationalization: A Critical Appraisal 4. Frames for Internationalizing Media Research 5. Media and Communication Studies Going Global. Part II. Broadening the Field of Media Studies 6. Globalizing Media Law and Policy 7. Changing Paradigms of Media Research and Practice in Contexts of Globalization and Terror 8. Comparative Media Law and Policy: Opportunities and Challenges 9. The Labouring of International Communication. Part III. Regional Perspectives on Internationalization 10. Asian Media Studies: The Struggle for International Legitimacy 11. Rethinking Chinese Media Studies: History, Political Economy and Culture 12. Media and Cultural Studies in the Arab World: Making Bridges to Local Discourses of Modernity 13. De-Sovietizing Russian Media Studies 14. Citizens’ Media as Political Subjects: Case of Community Radio in Colombia. Part IV. Pedagogic Parameters: Internationalizing Media Syllabi 15. Internationalizing Media Ethics Studies 16. Media Studies as an Academic Discipline 17. International Media Studies in the US Academy: A Sampling of Programmes and Textbooks 18. Re-Conceptualizing Media Studies in Africa 19. The Internationalization of the Internet and its Implications for Media Studies.